A microscopy-based small molecule screen in primary neurons reveals neuroprotective properties of the FDA-approved anti-viral drug Elvitegravir - Merz, Simon; Bengtson, C. Peter; Tepohl, Clara; Hertle, Anna M.; Bading, Hilmar; Bas Orth, Carlos (Molecular brain, 2020)
Glutamate toxicity is a pathomechanism that contributes to neuronal cell death in a wide range of acute and chronic neurodegenerative and neuroinflammatory diseases. Activation of theN-methyl-D-aspartate (NMDA)-type glutamate receptor and breakdown of the mitochondrial membrane potential are key events during glutamate toxicity. Due to its manifold functions in nervous system physiology, however, the NMDA receptor is not well suited as a drug target. To identify novel compounds that act downstream of toxic NMDA receptor signaling and can protect mitochondria from glutamate toxicity, we developed a cell viability screening assay in primary mouse cortical neurons. In a proof-of-principle screen we tested 146 natural products and 424 FDA-approved drugs for their ability to protect neurons against NMDA-induced cell death. We confirmed several known neuroprotective drugs that include Dutasteride, Enalapril, Finasteride, Haloperidol, and Oxybutynin, and we identified neuroprotective properties of Elvitegravir. Using live imaging of tetramethylrhodamine ethyl ester-labelled primary cortical neurons, we found that Elvitegravir, Dutasteride, and Oxybutynin attenuated the NMDA-induced breakdown of the mitochondrial membrane potential. Patch clamp electrophysiological recordings in NMDA receptor-expressing HEK293 cell lines and primary mouse hippocampal neurons revealed that Elvitegravir does not act at the NMDA receptor and does not affect the function of glutamatergic synapses. In summary, we have developed a cost-effective and easy-to-implement screening assay in primary neurons and identified Elvitegravir as a neuro- and mitoprotective drug that acts downstream of the NMDA receptor.